Venous Thromboembolism In Cancer Patients: "From Evidence to Care". (May 2022) - Salgado, Mercedes; Brozos-Vázquez, Elena; Campos, Begoña; González-Villarroel, Paula; Pérez, María Eva; Vázquez-Tuñas, María Lidia; Arias, David
This article seeks to review the current status of treatment and prevention of venous thromboembolic disease (VTE) in cancer patients after the addition of direct oral anticoagulants (DOAC) to the therapeutic arsenal available. The suitability of DOAC use in complex clinical situations, poorly represented in clinical trials, is controversial and difficult for care activity, making the recommendations in clinical practice guidelines the focus of special attention in this area. Recently, several randomized trials have compared low molecular weight heparin (LMWH) to DOAC for the management of CAT. Potential drug interactions with DOACs or the increased risk of bleeding in intraluminal tumors require special precautions, as do metastatic or primary brain disease and comorbid conditions, such as renal or liver failure, which are not suitably represented in pivotal studies. Furthermore, few data are available for situations involving elevated bleeding risk, with thrombocytopenia levels below the inclusion criterion of clinical trials, or recurrence during active anticoagulant therapy. Similarly, it is less clear that patients and physicians accept the presumption that oral DOAC administration is more convenient than subcutaneous LMWH, particularly when drug absorption may be compromised. The non-inclusion or under-representation of patients at higher risk for complications with anticoagulation in randomized clinical trials, makes their use complex in certain situations in health care. This paper provides a practical review of current clinical guideline recommendations regarding LMWH and/ or DOAC to treat and prevent CAT, as well as the most controversial clinical conditions for their use.